2011
DOI: 10.1111/j.1471-0528.2011.02941.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental tobacco smoke on perinatal outcomes: a retrospective cohort study

Abstract: Exposure of nonsmoking pregnant women to ETS is associated with a number of adverse perinatal outcomes including lower birthweight, smaller head circumference and stillbirth, as well as shorter birth length. This information is important for women, their families and healthcare providers, and reinforces the continued need for increased public policy and education on prevention of exposure to ETS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 15 publications
1
39
1
1
Order By: Relevance
“…This study is consistent with previous studies indicating that exposure to SHS during pregnancy significantly reduced birthweight. Other studies 5,11,28,34 showed an association between LBW and SHS.…”
Section: Exposure To Secondhand Smoke During Pregnancy and Lbwmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is consistent with previous studies indicating that exposure to SHS during pregnancy significantly reduced birthweight. Other studies 5,11,28,34 showed an association between LBW and SHS.…”
Section: Exposure To Secondhand Smoke During Pregnancy and Lbwmentioning
confidence: 99%
“…SHS ϭ second hand smoke LBW ϭ low birthweight NR ϭ not reported pregnancy, 5,6 to quantity of exposure to SHS, 11,13,[24][25][26][27][28][29][30][31][32][33]35,36 and to cotinine level (Tables 1 and 2). 12,14,17,22,37 One study 10 confirmed that exposure to SHS during pregnancy was a cause of LBW and not merely an association.…”
Section: Exposure To Secondhand Smoke During Pregnancy and Lbwmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, studies have associated maternal secondhand smoke exposure with low infant birth weight and congenital anomalies (Salmasi, Grady, Jones, McDonald, & Knowledge Synthesis, 2010), increased risk of stillbirth, small infant head circumference (Crane, Keough, Murphy, Burrage, & Hutchens, 2011), and SIDS (U.S. Department of Health and Human Services, 2006).…”
Section: Introductionmentioning
confidence: 99%